A MULTINOMIAL LOGIT MODEL FOR ESTIMATING THE INFLUENCE OF HOUSEHOLD CHARACTERISTICS ON MOTORCYCLE OWNERSHIP: A Case Study in Denpasar City, Bali - D. M. Priyantha Wedagama (Institut Teknologi Sepuluh Nopember, 2009)
This study investigates on household factors which influence motorcycle ownership in Denpasar city, Bali by using a multinomial logit model. The analyses show that the number of family members were about 0.83 and 2.6 times more likely to own, respectively, two and three motorcycles or more than one motorcycle. Total household income of less than one million rupiahs and between one and two million rupiahs were respectively 83.7 and 84.7 percents less likely to influence three motorcycles or more than one motorcycle ownership. Meanwhile, due to its high maneuverability on the congested road, a household was about 3.3 times more likely to own three motorcycles or more than one motorcycle. The probability analyses present that a double change in number of family member could influence one, two, and three motorcycles ownership or more by 19, 34, and 48 percents, respectively.